2011
DOI: 10.1364/ao.50.000981
|View full text |Cite
|
Sign up to set email alerts
|

Mirror tilt immunity interferometry with a cat’s eye retroreflector

Abstract: This paper describes the behavior of a cat's eye retroreflector, which is incorporated in a novel way in a double-pass homodyne polarization interferometer. The amount of mirror tilt immunity a cat's eye provides is calculated within the paraxial approximation using 4×4 ABCD matrices. It is found that there is a position of the target mirror in which the tilt immunity is at a maximum. A real cat's eye, which is affected by aberrations, is optimized and examined using Zemax software for optical design. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As can be seen in Fig. 1, we have inverted the lenses in the quasi cat's eye, compared with previous conventional designs [3]. Comparing the performance of the new design with a conventional cat's eye optical configuration, it was shown that only the quasi cat's eye is able to achieve the long working distance with unequal arm lengths required for this application (for more detail, see [1]).…”
Section: A Mirror Tilt Immunitymentioning
confidence: 95%
See 1 more Smart Citation
“…As can be seen in Fig. 1, we have inverted the lenses in the quasi cat's eye, compared with previous conventional designs [3]. Comparing the performance of the new design with a conventional cat's eye optical configuration, it was shown that only the quasi cat's eye is able to achieve the long working distance with unequal arm lengths required for this application (for more detail, see [1]).…”
Section: A Mirror Tilt Immunitymentioning
confidence: 95%
“…6 shows the visibility for only one position of the target mirror -the 'sweet plane', where the greatest visibility is achievable (see [1] for more detail). As :iiin the target mirror is moved away from the sweet plane, we expect the visibility to linearly decrease, as it does in the EUCLID interferometer [2,3]. These results will be presented in a later paper, currently in preparation [6].…”
Section: Component Specificationmentioning
confidence: 97%
“…When there is an exact multiple of fringe lines within the active area [18], the radiant flux across the active area is the mean of the maximum constructive and destructive interferences, i.e. , 50%.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…To overcome or minimise mirror tilt prevalent with flat plane mirrors, corner cube retro-reflectors [8,9], cat-eye reflectors [18] or alternate interferometers [11] are used.…”
Section: Introductionmentioning
confidence: 99%
“…When these optoelectronic devices are illuminated by a laser, the echo wave is higher than the diffuse targets by 2-4 orders of magnitude, on average [1,2]. Detecting and recognizing cat-eye effect targets is an important technique in military reconnaissance [3], anticandid cameras [4], free-space communication [5][6][7], optoelectronic device identification and tracking [8,9], laser range finding [10], etc. In recent years, some methods have been developed to recognize cat-eye effect targets.…”
Section: Introductionmentioning
confidence: 99%